2018
DOI: 10.1029/2018jb016064
|View full text |Cite
|
Sign up to set email alerts
|

A Pedogenic Model for the Magnetic Enhancement of Late Miocene Fluvial‐Lacustrine Sediments From the Xining Basin, NE Tibetan Plateau

Abstract: Continuous sequences of Cenozoic fluvial‐lacustrine sediments are well preserved in the northeastern edge of the Tibetan Plateau (TP), and they provide a good opportunity to improve our understanding of the tectonic uplift and paleoenvironmental evolution of the NE TP. To date, however, the factors controlling the variations in the magnetic properties of these fluvial‐lacustrine sediments remain complex and ambiguous. Here we systematically assess the contribution of pedogenesis to the magnetic enhancement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
(184 reference statements)
0
8
0
Order By: Relevance
“…B. Yang, Galy, et al, ), the North Pacific (Rea et al, ), the South China Sea (Wan et al, ), and the Japan Sea (Shen et al, ), indicating enhanced aridification in central Asia and/or more dust available on the source areas (e.g., Nie et al, ). Magnetic enhancements could also be seen in the Qaidam Basin (Nie et al, ), the Jianzha Basin (Fu et al, 2017), the Xining Basin (Zan et al, ), the Linxia Basin (Yan et al, ), and the CLP (Nie et al, ) at ~8 Ma, yet the mechanisms of this enhancement are still debated. Eolian dust input (Fu et al, 2017; Nie et al, ), provenance change (Yan et al, ), and pedogenic enhancement (Zan et al, ) are all thought to be the main potential factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Yang, Galy, et al, ), the North Pacific (Rea et al, ), the South China Sea (Wan et al, ), and the Japan Sea (Shen et al, ), indicating enhanced aridification in central Asia and/or more dust available on the source areas (e.g., Nie et al, ). Magnetic enhancements could also be seen in the Qaidam Basin (Nie et al, ), the Jianzha Basin (Fu et al, 2017), the Xining Basin (Zan et al, ), the Linxia Basin (Yan et al, ), and the CLP (Nie et al, ) at ~8 Ma, yet the mechanisms of this enhancement are still debated. Eolian dust input (Fu et al, 2017; Nie et al, ), provenance change (Yan et al, ), and pedogenic enhancement (Zan et al, ) are all thought to be the main potential factors.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic enhancements could also be seen in the Qaidam Basin (Nie et al, ), the Jianzha Basin (Fu et al, 2017), the Xining Basin (Zan et al, ), the Linxia Basin (Yan et al, ), and the CLP (Nie et al, ) at ~8 Ma, yet the mechanisms of this enhancement are still debated. Eolian dust input (Fu et al, 2017; Nie et al, ), provenance change (Yan et al, ), and pedogenic enhancement (Zan et al, ) are all thought to be the main potential factors. Despite multiple mechanisms, such modifications may reflect complex responses of fluvial and atmospheric systems to climate‐tectonic coupling at ~8 Ma on the northeastern TP and the CLP (e.g., Nie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This differential uplift may explain the decoupling of the sustainable aridification and short-term uplift events throughout the Mid to Late Miocene. The uplift of the Xining Basin during thẽ 10.5-to 8-Ma period would have strongly affected the regional environment and led to the enhanced aridification suggested by rock magnetic records (Zan et al, 2018), clay mineral records (R. Yang et al, 2019), and our reconstructed paleo-pH and microbial lipid ratio values (see section 3.2). Furthermore, the divergence in the oxygen isotopic values observed between the Xunhua and Linxia basins, located on either side of the Jishi Mts.…”
Section: Climate Change Driven By Uplift and Co 2 Levelsmentioning
confidence: 93%
“…However, climate change can also affect erosion by controlling the vegetation that protects the Earth's surface from erosion; conversely, climate change can also affect precipitation levels that can in turn strengthen erosion (P. Zhang et al, ; Nie et al, ). Also, the magnetic susceptibility, clay mineral, and element indicators all appear to have changed simultaneously at ~9 Ma (Ruan et al, ; Zan et al, ; R. Yang et al, ), asynchronous with the increases in sedimentation rates. Our data indicate that the drought in the Xining Basin reached a certain statistical point (i.e., MAP <600 mm) at ~9 Ma during the cooling process.…”
Section: Cooling and Upliftmentioning
confidence: 99%
“…Recently, it was reported that the MMCO can be identified using pollen records (Sun JM and Zhang ZQ, 2008; Larsson et al, 2011; Miao YF et al, 2011; Hui ZC et al, 2018), geochemical records (Wan SM et al, 2009; Song YG et al, 2018), and magnetic records (Zan JB et al, 2015; Guan C et al, 2019). Compared with investigations of other climatic proxies, studies of environmental magnetism are convenient, nondestructive, and effective in treating loess‐paleosol sequences (Heller and Tungsheng, 1984; Verosub et al, 1993; Sun JM and Liu TS, 2000; An ZS et al, 2001; Guo ZT et al, 2002; Deng CL et al, 2005, 2006; Liu QS et al, 2007; Hao QZ et al, 2008) and fluviolacustrine sediments (Jiang HC et al, 2008; Ao H et al, 2010; Song CH et al, 2014; Fang XM et al, 2015; Zhang T et al, 2016; Fu CF et al, 2018; Zan JB et al, 2018), enabling us to reconstruct past climatic changes. Therefore, we performed rock magnetic measurements in the Tiejianggou Section.…”
Section: Introductionmentioning
confidence: 99%